Providing health services effectively during the first wave of COVID-19: A cross-country comparison on planning services, managing cases, and maintaining essential services. Issue 5 (May 2022) - Webb, Erin; Hernández-Quevedo, Cristina; Williams, Gemma; Scarpetti, Giada; Reed, Sarah; Panteli, Dimitra
Highlights: Health care providers worldwide faced immediate challenges triggered by the COVID-19 pandemic. Despite substantial differences in health system provision, countries had many similar responses. Initially, many countries hospitalized COVID-19 patients, but increasingly transitioned to outpatient care. Remote consultations and cancelling or postponing non-urgent treatments were common adaptations. Service delivery modifications during COVID-19 may become permanent features of care provision. Abstract: The COVID-19 pandemic triggered abrupt challenges for health care providers, requiring them to simultaneously plan for and manage a rise of COVID-19 cases while maintaining essential health services. Since March 2020, the COVID-19 Health System Response Monitor, a joint initiative of the European Observatory on Health Systems and Policies, the WHO Regional Office for Europe, and the European Commission, has documented country responses to COVID-19 using a structured template which includes a section on provision of care. Using the information available on the platform, this paper analyzes how countries planned services for potential surge capacity, designed patient flows ensuring separation between COVID-19 and non-COVID-19 patients, and maintained routine services in both hospital and ambulatory settings. Despite very real differences in the organization of health and care services, there were many similarities in country responses. These include transitioning the management of COVID-19 mild cases from hospitals to outpatient settings, increasing the use of remote consultations, and cancelling or postponing non-urgent services during the height of the first wave. In the immediate future, countries will have to continue balancing care for COVID-19 and non-COVID-19 patients to minimize adverse health outcomes, ideally with supporting guidelines and COVID-19-specific care zones. Looking forward, policymakers will have to consider whether strategies adopted during the COVID-19 pandemic will become permanent features of care provision.